2017
DOI: 10.1055/s-0037-1608921
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exon Deletion in the GFAP Gene Is a Novel Molecular Mechanism Causing Alexander Disease

Abstract: Alexander disease (AD) is a leukodystrophy caused by heterozygous mutations in the gene encoding the glial fibrillary acidic protein (GFAP). Currently, de novo heterozygous missense mutations in the gene are identified in over 95% of patients with AD. However, patients with biopsy-proven AD have been reported in whom no mutation has been identified. We report identical twin boys presenting in infancy with seizures and developmental delay in whom MR appearances were suggestive of AD with the exception of an unu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…For individual II:1, family 3, a heterozygous deletion of the entire coding region of DLX3 was detected by comparative NGS read‐depth analysis (Green et al, ). After correcting for sample‐to‐sample variation in each of the samples in the same sequencing lane ( n = 8), read depths across DLX3 exons for individual II:1 were compared to the median value for the dataset, effectively using the other seven sequenced samples in the lane as a control data set for the patient sample.…”
Section: Resultsmentioning
confidence: 99%
“…For individual II:1, family 3, a heterozygous deletion of the entire coding region of DLX3 was detected by comparative NGS read‐depth analysis (Green et al, ). After correcting for sample‐to‐sample variation in each of the samples in the same sequencing lane ( n = 8), read depths across DLX3 exons for individual II:1 were compared to the median value for the dataset, effectively using the other seven sequenced samples in the lane as a control data set for the patient sample.…”
Section: Resultsmentioning
confidence: 99%
“…(Quinlan, Brenner, Goldman, & Messing, 2007;Yasuda et al, 2019) Alexander disease is considered a gain-of function disorder in the sense that the GFAP mutations produce consequences that differ dramatically from those caused by the absence of GFAP (like that case in this study).Although the main cause of sever and lethal AxD is accumulation of toxic defective proteins in astrocytes as a consequence of point mutation in GFAP gene; but, in this case with deletion of 1-9 exons, GFAP protein is produced from intact allele with less than 50% performance-This phenomenon is called haploinsufficiencybesides, previous studies demonstrated that deletion of some exons like exon 5. (Green, 2018) After a pathogenic mutation is discovered, it is preferred to assess mutation in other family members, whom could be asymptomatic or minimally affected.…”
Section: Discussionmentioning
confidence: 99%
“…For individual II:1, family 3, a heterozygous deletion of the entire coding region of DLX3 was detected by comparative NGS read-depth analysis (Green et al, 2017). After correcting for sample-to-sample variation in each of the samples in the same sequencing lane (n = 8), read depths across DLX3 exons for individual II:1 were compared to the median value for the dataset, effectively using the other seven sequenced samples in the lane as a control data set for the patient sample.…”
Section: Re Sultsmentioning
confidence: 99%